AB0740 The frequency of occult hepatitis b infection in rheumatic diseases and the role of anti-hbc test in routine practice. (23rd January 2014) - Yilmaz, S.; Sener, K.; Simsek, I.; Cinar, M.; Gumral, R.; Erdem, H.; Kubar, A.; Pay, S.
Abstract : Background: Most of the drugs used in rheumatic diseases suppress the immune system, especially corticosteroids and anti-TNF agents, therefore may cause reactivation in patients with hepatitis B virus (HBV). Studies have shown that HBV reactivation due to immunosuppression is not a case only in patients with chronic HBV infection, but also in patients with occult diseases. The presence of HBV DNA in liver tissue and/or in serum in the absence of detectable hepatitis B surface antigen (HBsAg) is called occult HBV infection. Evidence is accumulating that HBV is present in patients who are HBsAg negative, but have antibody to hepatitis B core antigen (anti-HBc) Therefore, guidelines recommend that anti-HBc IgG tests should be added to HBsAg and anti-HBs tests before initiation of immunosuppressive therapy. Objectives: In the present study we aimed to determine the prevalence of occult HBV infection in patients receiving immunosuppressive agents and examine the role of anti-HBc as a screening test for occult infection in Turkish patients with rheumatic diseases. Methods: Consecutive patients using immunosuppressive agents for rheumatic diseases seen in rheumatology outpatient clinic and who are negative for HBsAg were included. The demographic features, received treatment in last 3 months and liver function tests of all patients were recorded. HBsAg, Anti-HBs and anti-HBc IgG tests were studied in all participants along with the quantification of HBV-DNA by real-time PCR. Results: Total 116 patients included to the study (59 spondylarthritis, 39 romatoid arthritis, and 18 others). The demographic features and received treatment in last 3 months were presented in Table 1 . In this HBsAg negative group, 27 patients (23%) were found to be positive for anti-HBc IgG. In this subgroup, 19 patients were anti-HBs Ab positive while isolated anti-HBc IgG positivity were detected in other 8 patients. None of the patients was found as HBV-DNA positive. Conclusions: Since none of our patients with isolated anti-HBc positivity had detectable levels of HBV-DNA in their serum, using anti-HBc test for screening seems not to be justified. While our results suggest that prevalence of occult HBV infection is ignorable among patients with rheumatic diseases in Turkey, considering the preliminary feature of our results (target study population is 300) full results should be waited to reach such a definite conclusion. Disclosure of Interest: None Declared